Dermoscopy makes the diagnosis of alopecia areata easier. - d’Ovidio, R.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Dermoscopy makes the differential diagnosis of the various forms of alopecia easier (1, 2). Particularly, alopecia areata is dermoscopically characterized by exclamation mark hairs and cadaverized hairs (blackish dots). Moreover, there are yellow dots, namely roundish and yellowish areas, centered or not by a hair, corresponding to dilated follicular orifices (Fig. 3) filled in with sebum and/or fragments of hairs. The yellow dots are characteristic of alopecia areata and tend to regress in the phase of remission, thanks to the cleaner effect of the regrowing hair. The yellow dots can be found in 95% of cases of recent alopecia areata and in 90% of cases of acute, diffuse and total alopecia of the female scalp, a subtype of alopecia areata, characterized by female prevalence and rapid progression (3). Only rarely they can be found in case of advanced androgenic alopecia in the male subjects.